THE EFFECT OF COVID-19 PANDEMIC ON THE TOURISM TRAVEL AND RISK MANAGEMENT IN THAILAND - Tunwarat Kongnun; Sudarat Rattanapong; Chonticha Yuphuang; Pongpon Puttivisit; Maneejan Masoot (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The study aims to measure the effect of the COVID-19 pandemic on tourism travel and risk management in Thailand. This review utilised journals, historical records, newspaper articles, World Health Organization statistics, governmental data, and website materials on COVID-19 incidences in tourism and developed a new risk management method to deal with the crisis and post-crisis recovery. The objectives were to: 1) understand how tourism travel regain after the Covid crisis, 2) find out the opinions of tourism travel about the tourism opportunities after the COVID-19 crisis.; 3) explore the ideas on how tourism travel will adjust or adapt to fit with a shift in travel priorities after the COVID-19 pandemic. The purposive sampling method was used data through in-depth interviews with hotel and restaurant operations. During Aug-Sept 2020 in the provinces that are the most controlled areas are Bangkok and Chiang Mai, the qualitative data were analysed using Grounded Theory by symbolic interaction. According to the main finding, hygiene and safety are the most important priorities for tourists when they can travel again so the use of hygiene and safety protocols along with the collaboration with the public sector, and the support from the government. Also, crisis management strategies and risk management departments are vital for tourism travel to deal with challenges after the crisis.